Development of a Model and Implementation of a Shadow Puppet-Based Sports Game to Introduce Shadow Puppets to Adolescents - Antonius Tri Wibowo; Yustinus Sukarmin; Sugeng Purwanto; Yulius Agung Saputro; Febri Sulistiya (Jan Długosz University in Częstochowa, 2024)
Shadow puppets are starting to be abandoned by teenagers in Indonesia due to globalization. This study aims to develop a Javanese shadow puppet-based sports game to introduce shadow puppets to teenagers - Borg & Gall development research. The research stages are preliminary studies, validation assessment by six experts in the field of sports games, shadow puppet experts, and graphic design experts. Validation using the Delphi technique, with data analysis using Aiken's V content validity coefficient. Furthermore, the trial stage with a sample of 34 adolescents aged 12-19 years, divided into 14 on a small scale trial and 20 on a large scale trial. The data collection technique used a survey with a questionnaire instrument using Likert scale with a score range of 1-5. The results of this study produced a Javanese Kigfun Game (J-KIG), a sports game product that combines soccer and softball sports games with shadow puppet characters from the Ramayana story. The J-KIG game obtained valid results with a score of 0.8-1. The small-scale trial received a feasibility assessment of 87% with the criteria "Very Feasible," while the large-scale trial obtained a feasibility assessment of 84% with the terms "Feasible."